Serum testosterone levels and other determinants of sperm retrieval in microdissection testicular sperm extraction - Althakafi, Sultan A.; Mustafa, Osama M.; Seyam, Raouf M.; Al-Hathal, Naif; Kattan, Said (Translational Andrology and Urology; Vol 6, No 2 (April 29, 2017): Translational Andrology and Urology (Global Urology), 2017)
Background: Microdissection testicular sperm extraction (microTESE) has become the standard of care for sperm retrieval in non-obstructive azoospermia (NOA) patients. Understanding the significant determinants of microTESE outcomes may result in improvements in sperm retrieval rates and provide better-informed clinical decisions. Methods: This is a clinical retrospective study conducted through chart review of 421 NOA patients who underwent microTESE between August 2009 and July 2015 in a tertiary-care referral hospital. Clinical, biochemical and histopathological characteristics were collected. Normal serum testosterone level was defined as testosterone >9.9 nmol/L. Multiple logistic regression was used to identify determinants of microTESE in the studied population. A P